Hydrogen-induced hot workability in Ti-6Al-4V alloy - 宗影影 单德彬 吕炎 郭斌 (Transactions of Nonferrous Metals Society of China, 2006)
The effect of hydrogen on hot deformability of Ti-6Al-4V alloy was investigated by isothermal hot compression test with temperature of 800 ℃ and velocity of 0.1 mm/s. By optical microscopy （OM） and transmission electron microscopy （TEM）, the influence of hydrogen on the microstructural features was systematically examined including the morphology of a grain, volume fraction of a phase and dynamic recrystallization （DRX）. The flow stress shows an initial decrease but a later increase with the increase of hydrogen content. The minimum of peak compression flow stress is obtained when 0.2% hydrogen is added into the alloy. The hydrogen-induced softening of Ti-6Al-4V alloy may be that hydrogen induces the increase of proportion of soft β phase, the increase of DRX and the increase of extent of twins.